2021
DOI: 10.1021/acsphotonics.0c01412
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Photoemission from Single-Crystalline Silver

Abstract: Optical fields interacting with solids excite single particle quantum transitions and elicit collective screening responses that define their penetration, absorption, and reflection. The interplay of these interactions on the attosecond time scale defines how optical energy transforms to electronic, setting the limits of efficiency for processes such as solar energy harvesting or photocatalysis. Our understanding of light–matter interactions is primarily based on specifying the electronic structure of solids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 141 publications
3
35
0
Order By: Relevance
“…In particular, it is shown that under excitation with photon energies matching the bulk plasmon energy, the bulk plasmon decay preferentially excites photoelectrons from the Fermi level rather than producing a broad energy distribution of hot electrons and holes, a process referred to "plasmonic photoemission". [44] In our setup, with pump photon energy much lower than bulk plasmon energy, this phenomenon cannot be observed.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In particular, it is shown that under excitation with photon energies matching the bulk plasmon energy, the bulk plasmon decay preferentially excites photoelectrons from the Fermi level rather than producing a broad energy distribution of hot electrons and holes, a process referred to "plasmonic photoemission". [44] In our setup, with pump photon energy much lower than bulk plasmon energy, this phenomenon cannot be observed.…”
Section: Discussionmentioning
confidence: 77%
“…Concerning the nonthermal carriers, recent experiments report that the actual distribution of non-thermal carriers in a plasmonic metal [44] may differ from the calculated ones for example, in refs. [48] and [49].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[7,[51][52][53] for an overview): highly energetic nonthermal carriers and thermalized hot carriers, described in terms of the electronic temperature ϑ e . Concerning the nonthermal carriers, recent experiments report that the actual distribution of non-thermal carriers in a plasmonic metal [44] may differ from the calculated ones in e.g. [48] and [49].…”
Section: Discussionmentioning
confidence: 91%
“…The current understanding of ultrafast relaxation processes in plasmonic nanosystems rests upon ultrafast time-resolved optical and, to a lesser extent, electronic spectroscopies, [28,[37][38][39][40] that however mostly yield indirect information about the time-dependent electron-gas or ion-lattice temperature [41,42]. Theoretical models, on the other hand, are becoming more and more refined, yet cannot handle, so far, the complexity of real systems [3,15,22,43,44]. In this work, we report the measurement of the ultrafast electron-temperature (ϑ e ) dynamics within an ensemble of plasmonic gold NPs, laid onto a transparent conductive oxide support, thereby allowing to perform photoemission experiments while allowing a degree of electron confinement sufficient to preserve the LSP resonance.…”
Section: Introductionmentioning
confidence: 99%